Plasmon‐Enhanced Fluorescence‐Based Core–Shell Gold Nanorods as a Near‐IR Fluorescent Turn‐On Sensor for the Highly Sensitive Detection of Pyrophosphate in Aqueous Solution. (29th October 2015) - Wang, Le; Song, Quanwei; Liu, Qiuling; He, Dacheng; Ouyang, Jin
Abstract : Developing plasmon‐enhanced fluorescence (PEF) technology for identifying important biological molecules has a profound impact on biosensing and bioimaging. However, exploration of PEF for biological application is still at a very early stage. Herein, novel PEF‐based core–shell nanostructures as a near‐infrared fluorescent turn‐on sensor for highly sensitive and selective detection of pyrophosphate (PPi) in aqueous solution are proposed. This nanostructure gold nanorod (AuNR)@SiO2 @ meso ‐tetra(4‐carboxyphenyl) porphyrin (TCPP) contains a gold nanorod core with an aspect ratio of 2.3, a silica shell, and TCPP molecules covalently immobilized onto the shell surface. The silica shell is employed a rigid spacer for precisely tuning the distance between AuNR and TCPP and an optimum fluorescence enhancement is obtained. Due to the quenching effect of Cu 2+, the copper porphyrin (TCPP‐Cu 2+ ) results in a weak fluorescence. In the presence of PPi, the strong affinity between Cu 2+ and PPi can promote the disassembly of the turn‐off state of TCPP‐Cu 2+ complexes, and therefore the fluorescence can be readily restored. By virtue of the amplified fluorescence signal imparted by PEF, this nanosensor obtains a detection limit of 820 × 10 −9 m of PPi with a good selectivity over several anions, including phosphate. Additionally, the potential applicability of this sensor in cell imaging is successfully demonstrated. Abstract : Core–shell gold nanorods are employed to significantly enhance the fluorescence intensity of meso ‐tetra(4‐carboxyphenyl) porphyrin via the plasmon‐enhanced fluorescence effect. These nanostructures combined with the quenching effect of Cu 2+ are applied to turn‐on detection of pyrophosphate with nanomolar sensitivity in aqueous solutions, which may provide great potential for the development of highly sensitive sensing systems in biological and biomedical applications.